People of Destiny : Eleanor Roosevelt - Richards, Kenneth G. (Chicago, Childrens Press, 1968)
1. Roosevelt, Eleanor 2. A biography of Eleanor Roosevelt, whose efforts to aid her husband in his work, in spite of her shyness, made her one of the most admired First Ladies in history.
Includes Bibliography & index
Bibliography: p. 90-91.
Basic Ed. Students
Keywords: Roosevelt, Eleanor, -- 1884-1962 -- Juvenile literature; Roosevelt, Eleanor, -- 1884-1962.; First ladies; Women -- Biography